Sifat Fisis dan Mekanis Oriented Strand Board Hibrida Bambu Pada Berbagai Shelling Ratio (Physical and Mechanical Properties of Hybrid Bamboo Oriented Strand Board at Various Shelling Ratios) - Rynaldo Davinsy; Sena Maulana; Muhammad I Maulana; Elvara D Satria; Deded S Nawawi; Rita K Sari; Wahyu Hidayat; Fauzi Febrianto (Masyarakat Peneliti Kayu Indonesia, 2019)
Hybrid Bamboo Oriented Strand Boards (OSB) were produced to improve bamboo OSB's physical and mechanical properties. Shelling ratio adjustment of the strand type combination could determine the optimal physical and mechanical properties of hybrid bamboo oriented strand boards (OSB). The purpose of this study was to evaluate the physical and mechanical properties of hybrid betung and andong bamboos OSB at various shelling ratios. Steam modified strands of betung and andong bamboo were used as an outer layer and core layer, respectively. Hybrid bamboo OSBs were prepared with 0.7 g cm-3 target density and 8% phenol-formaldehyde resin content. Three layers of OSB were made with outer: core shelling ratios of 30:70, 40:60, 50:50, and 60:40. The physical and mechanical properties of the OSB were tested referring to the JIS A 5908-2003 standard. The targeted board density was achieved and the physical properties of all hybrid bamboo OSB have met the requirement of CSA O437.0 (Grade O-1) standard criteria. The parallel modulus of elasticity (MOE) and modulus of rupture (MOR) increased with increasing outer layer ratio. However, the perpendicular MOE and MOR decreased with increasing outer layer ratio. The internal bonding (IB) of the OSB with a shelling ratio of 30:70 and 40:60 met with the requirement of the CSA O437.0 (Grade O-1) standard.